Parameters of dual task walking in patients with stroke: a scoping review. - Sakai, Katsuya; Hosoi, Yuichiro; Harada, Yusuke (Physical Therapy Reviews, 2025)
Introduction: This study aimed to chart the parameters of dual-task (DT) walking in patients with stroke. Methods: We searched five databases (PubMed, Web of Science, CINAHL, MEDLINE, and Cochrane Library). The population, concept, and context included patients with stroke as the population; DT walking, observational studies, and randomized controlled trials (RCTs) as the concept; and walking speed, DT walking cost, and walking parameters (stride length, step length, cadence, and variability) as the context. Results: A total of 780 papers were extracted, and eight were included. The study design included observational studies (50%) and RCTs (50%), with 220 patients analyzed. The type of DT walking was either a subtraction or a carrying task. We found that walking speed, stride length, and step length were decreased, and gait variability was higher during DT walking compared to single-task walking. Discussion: This scoping review charted walking parameters during DT walking in patients with stroke.